On the symmetry of ionospheric polar cap patch exits around magnetic midnight. Issue 9 (4th September 2015) - Moen, J.; Hosokawa, K.; Gulbrandsen, N.; Clausen, L. B. N.
Abstract In this paper we examine how polar cap patches, which have been frozen into the antisolar flow over the polar cap, are transported into the nighttime auroral oval. First we present a detailed case study from 12 January 2002, with continuous observations of polar cap patches exiting into the nighttime auroral oval in the Scandinavian sector. Satellite images of the auroral oval and all‐sky camera observations of 630.0 nm airglow patches are superimposed onto Super Dual Auroral Radar Network convection maps. These composite plots reveal that polar cap patches exit on both the dusk and on the dawn convection cells. Then we present statistics based on 8 years of data from the meridian scanning photometer at Ny‐Aalesund, Svalbard, to investigate the possible interplanetary magnetic field (IMF) By influence on the distribution of patch exits around magnetic midnight. The magnetic local time distribution of patch exits is almost symmetric around magnetic midnight, independent of IMF By polarity. Synthesizing these observations with previous results, we propose a three‐step mechanism for why patch material exits symmetrically around midnight. First, intake of patch material occurs on both convection cells for both IMF By polarities. Second, plasma intake by transient magnetopause reconnection stretches the newly cut polar cap patches into dawn‐dusk elongated forms during their transport into the polar cap. And finally at exit, dawn‐dusk elongated patches are split and diverted toward both the dawn and dusk flanks when grabbed by transient tail reconnection.